Implementation of Economic Value Added and Market Value Added Analysis as Valuation Tools of Invest Feasibility (Economic and Bussiness Faculty, Dr Soetomo University, 2017)
For the investors, financial statement is a benchmark of investors in assessing the company's performance. In fact, investors are not always receiving the accurate company's financial statements information and its levels of fairness are in doubt. The financial statement analysis with using financial ratios is not enough. The investors may need to use alternatives financial statement analyses techniques that reflect the actual company's performance. Therefore, both of the investors and the prospective can use Economic Value Added (EVA) and Market Value Added (MVA) analysis. With these technical analyses, the investors may know the company's performance where they are invested or to be used as a place to invest whether it has value added or not. With the results of these analyses, it is the expected for the investors to be more confident in making decision whether to buy, sell or hold the ownership in the company.